Implementation of Financial Performance of Non-Profit Entities Through ISAK 335 Case Study of the Al Mumtaza Kindergarten Foundation Bengkalis - Zeti Fitriyani; Husnul Muttaqin (Majapahit Journal of Islamic Finance and Management, 2025)
This research was conducted at the Al Mumtaza Bengkalis Kindergarten Foundation. The purpose of this study is to find out how the accounting of the pesantren is applied by the Al Mumtaza Bengkalis Kindergarten Foundation. In addition, the purpose of this study is to find out the obstacles faced in the implementation of ISAK 335 as well as solutions to the obstacles faced in the implementation of ISAK 335 at the Al Mumtaza Kindergarten Foundation. The data collection method used in this study is by means of interviews, observations, documentation and literature studies. Interviews, namely researchers conduct questions and answers directly with informants involved in the preparation of financial statements. Observation is by means of direct observation in the field and systematically taking data and recording matters related to interview activities. Documentation is documents owned by Yaysan TK Al Mumtaza such as income records, expenditure records, cash flow records and other data that support this research. The results of the research obtained show that the financial statements of the Al Mumtaza Kindergarten Foundation are not fully in accordance with the generally accepted principles in accounting and are not in accordance with ISAK 355.